2014
DOI: 10.2169/internalmedicine.53.2429
|View full text |Cite
|
Sign up to set email alerts
|

Spasm Provocation Tests Performed under Medical Therapy: A New Approach for Treating Patients with Refractory Coronary Spastic Angina on Emergency Admission

Abstract: Objective There are no objective methods for evaluating the severity of vasospasms in patients with refractory coronary spastic angina (R-CSA) under adequate medical therapy. We examined whether spasm provocation tests performed under adequate medication are useful for evaluating the severity of disease in R-CSA patients on emergency admission. Methods and ResultsWe performed spasm provocation tests before and after the administration of medical therapy in eight R-CSA patients, including one ventricular fibril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…Eschalier et al reported the clinical use of ergonovine tests under the optimal medications when cardiologists considered the necessity of ICD implantation in patients with aborted SCD due to coronary spasm ( 32 ). We also reported the results of pharmacological spasm provocation testing under patients with refractory spasm who were treated with medical therapy ( 44 ). ICD implantation may not be always necessary for patients with aborted SCD who had life-threatening ventricular arrhythmia and coronary spasm.…”
Section: Discussionmentioning
confidence: 99%
“…Eschalier et al reported the clinical use of ergonovine tests under the optimal medications when cardiologists considered the necessity of ICD implantation in patients with aborted SCD due to coronary spasm ( 32 ). We also reported the results of pharmacological spasm provocation testing under patients with refractory spasm who were treated with medical therapy ( 44 ). ICD implantation may not be always necessary for patients with aborted SCD who had life-threatening ventricular arrhythmia and coronary spasm.…”
Section: Discussionmentioning
confidence: 99%
“…When the ergonovine test was negative under the optimum treatment conditions, they recommend individual discussion for ICD implantation; if the test was positive, they recommend ICD implantation in all cases, even if the optimum treatment was being administered. We also reported the findings of sequential spasm provocation tests in these near-miss patients under the optimum treatment conditions ( 10 ). If a positive provoked is not noted on a sequential spasm provocation test under optimum medical therapy in patients with aborted sudden cardiac death due to coronary spasm, cardiologists and patients are free to select a course of medical treatment without ICD implantation.…”
Section: Discussionmentioning
confidence: 99%
“…The spasm provocation data are shown in Table 2, and the total doses of precise vasodilators, including calcium channel blockers, are shown in Table 3. We have already reported three cases (case 2, 3, and 4) (12,13).…”
Section: Methodsmentioning
confidence: 97%